Edukasi Pencegahan Stunting di Kelurahan Pedurungan Tengah, Kota Semarang - Silvia Nurvita; Siti Noor Chotimah; Dody Indra Sumantiawan; Viny Natalia Dewi; Aerrosa Murenda Mayadilanuari (Pusat Riset dan Inovasi Nasional, 2024)
Stunting in children under five years old is a serious global health problem, especially in Semarang City. Community service activities were carried out in Pedurungan Tengah Village. The aim of this study was to increase the understanding about stunting and its prevention. Discussion method was used to deliver the topics, as well as distributing leaflets as a source of additional information. The results of the activity showed good participation from 32 participants. Active discussions showed participants' interest in understanding the topic of stunting. This community service also highlights the importance of maternal knowledge regarding stunting, considering that the risk of stunting increases in mothers with low knowledge. The implementation of the activity ended with an evaluation that showed satisfactory results. It is hoped that this community service can help increase public knowledge and awareness about stunting, as well as contribute to efforts to prevent stunting in Semarang City.